GE_GERICHTE C/24318/2013 vom 16. Oktober 2015 - GE Cour de justice (2015)
CAS CLAIR; ÉVACUATION(EN GÉNÉRAL); COMPÉTENCE RATIONE MATERIAE; CONTRAT DE CONCIERGERIE | CPC.257; LOJ.86.1; LOJ.86.2; LOJ.89.2; LOJ.89.1.a; CPC.59.1; CPC.59.2.b